The Challenge Of Integrating Corpus Linguistics Into Foreign Language Teaching - Radjabova Gulnoza Giyosiddinovna (Academia One Publishing, 2025)
This paper explores the theoretical and methodological aspects of integrating corpus linguistics into foreign language teaching. It examines the historical evolution of corpus linguistics, definitions of “corpus” by prominent linguists, and the epistemological foundations of corpusbased research. Emphasis is placed on the empirical nature of corpus linguistics and its growing potential as both a research method and an independent discipline. The paper argues for the pedagogical relevance of corpus tools in modern language education, highlighting their capacity to provide authentic linguistic data and foster data-driven learning. The shift from intuition-based teaching to evidence-based instruction is discussed in light of corpus technologies
Keywords: corpus linguistics; foreign language teaching; electronic corpora